ANGKA KELAHIRAN DI INDONESIA Perkembangan Selama Dua Dasa Warsa Terakhir - Sukamdi Sukamdi (Populasi, 1992)
Using "own children method", the Total Fertility Rate (TFR) in Indonesia based on the 1990 Population Census is lower (3326) than as hadbeen expected. This has resulted in the fast decrease of fertility rate during the last decade. There is a tendency that the decrease of fertility rate in Indonesia is correlated negatively to fertility rate. The lower the fertility rate, the faster the decrease would become. It tends to be a deviation to the usual concept that correlation between fertility rate and its decrease is positive.'This maybe because the fertility rate of Indonesia is still higher than the optimum value.Based on the decreases occurred during the last two decades, it is estimated that Indonesia will soon reach a replacement level after the year 2000. It might be even sooner if the decline of the fertility rate during the period of 1980-1990was applied. Along with the increase of life expectancy, this will rapidly change the population structure.The total fertility rate varied among provinces. There are several provinces which have very low fertility rate and are estimated to continue until the year 2000. They are, for instance,Yogyakarta and Bali. However, there are also provinces having high fertility rates such as Southeast Sulawesi and Irian Jaya. This differentiation infertility rates should be noted in implementing the population policy.